Dogs : from predator to protector - Hirsch, Andy, 1987- (Science comics (First Second (Firm)), 2017)
Offers scientific facts about the origins, evolution, genetics, physical traits, and behaviors of dogs in a full-color graphic novel format. Includes a glossary of terms and further resources.